1996
DOI: 10.1073/pnas.93.21.11877
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tracking of platelets: circulating degranulated platelets rapidly lose surface P-selectin but continue to circulate and function.

Abstract: To examine the hypothesis that surface Pselectin-positive (degranulated) platelets are rapidly cleared from the circulation, we developed novel methods for tracking of platelets and measurement of platelet function in vivo. Washed platelets prepared from nonhuman primates (baboons) were labeled with PKH2 (a lipophilic fluorescent dye), thrombin-activated, washed, and reinfused into the same baboons. Three-color whole blood flow cytometry was used to simultaneously (i) identify platelets with a mAb directed aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
412
7
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(454 citation statements)
references
References 26 publications
31
412
7
4
Order By: Relevance
“…Furthermore, labeling of platelets with biotin at either level or with PKH26 or PKH67 did not affect the responsiveness of the platelets to ADP, collagen, or thrombin, even at the lowest concentrations of agonists that did not give maximal responses. Our findings with the PKH dyes using in vitro platelet function testing by aggregometry and measurement of dense granule release are in keeping with the observations of Michelson et al (10). They found that PKH2 labeling of baboon platelets did not alter function as measured by flow cytometry in in vivo and ex vivo studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, labeling of platelets with biotin at either level or with PKH26 or PKH67 did not affect the responsiveness of the platelets to ADP, collagen, or thrombin, even at the lowest concentrations of agonists that did not give maximal responses. Our findings with the PKH dyes using in vitro platelet function testing by aggregometry and measurement of dense granule release are in keeping with the observations of Michelson et al (10). They found that PKH2 labeling of baboon platelets did not alter function as measured by flow cytometry in in vivo and ex vivo studies.…”
Section: Discussionsupporting
confidence: 92%
“…For labeling with lipophilic fluorescent dyes, the method of Michelson et al (10) was followed, with some modifications introduced during preliminary experiments to prevent platelet aggregation. Platelets recovered by centrifugation of platelet-rich plasma were resuspended in Diluent C, with added 15 M PGI 2 , at a platelet count of 4 ϫ 10 9 /ml.…”
Section: Preparation Of Platelet Suspensions For Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that activated platelets translate constitutive mRNAs into proteins [13][14][15]. Activation of platelets does not appear to decrease their life span [16][17][18], and this may be related to functional mRNAs in platelets. So it would be of interest to know the mRNA expression in platelets to better understand their gene regulatory mechanisms.…”
mentioning
confidence: 99%
“…LS174T cells were labeled with 2 M red fluorescent lipophilic membrane stain PKH26 according to the manufacturer's (Sigma) protocol, and platelets were similarly stained with 2 M green fluorescent PKH67 (Sigma) (28). HUVECs were incubated with 10 g/ml anti-ICAM-1 MAb for 30 min at 37°C before use in flow chamber assays.…”
Section: Allmentioning
confidence: 99%